Promosi Villa Kayu Putih - Satrianto Alpisa; Defrizal Saputra (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Villa kayu putih one of the villa that locate at Jorong Galagah Alahan Panjang, Lembah Gumanti Sub District, Solok Regency. Villa Kayu Putih do not have a catalog yet as a promotion and information media, thus making the customer having a hard time to obtain the information about facilities and service of Villa Kayu Putih. So the author decided to designing promotional media that is informative, communicative, useful and interesting to market the products to be offered. The design method used is the glass box method with SWOT analysis techniques. This design uses a simple concept where this style will make the information to be conveyed look clear and simple so it is easy to understand. The main media designed is e-catalog which will provide information about Villa Kayu Putih's products, facilities and services, also accompanied by other supporting media such as printed catalogs, Instagram content, posters, x-banners, stickers, t-shirts, business cards , and key chains.